Measuring customer satisfaction through perception study: a study of syarikat bekalan air Selangor sdn bhd (syabas) - S. Thayan, Vijaya Letchimi; Mat Asek, Baharuddin; Yusof, Radduan (2012)
The way a service is perceived and experienced will influence customer satisfaction. Customer perception is central to a service provider's success in an industry. This perceptions will be used to analyze the service quality dimension using an assessment tool called SERVPERV which was adopted from SERVQUAL. The SERVPERV model involves a set of 5 important dimensions of service quality, which are, tangibles, reliability, responsiveness, assurance and empathy. For the purpose of this research, the SERVPERV model was improvised by including water quality as one of the dimensions. The survey was conducted on 504 respondents across 10 districts of SYABAS operations covering domestic and industrial customers in Selangor, Kuala Lumpur and Putrajaya. The findings show a significant relationship between the perception of customers on all the quality dimension and customer satisfaction. The result showed that the most important dimension of service quality in SYABAS as how the customer perceived them are reliability followed by, tangibles, empathy, assurance, responsiveness and last but not least is the drinking water quality and this has show some similarity with the prior research. Adversely, in order for SYABAS to increase its service performance, they should focus more on the dimension that scored the less such as the drinking water quality and also the responsiveness. The result can be used to assist the agencies to improve their level of service to the customers.